Measurements of Water-Equivalent Diameter (Dw) Based on Localizer Radiograph for Tube Voltage Variation (International Journal of Scientific Research in Science and Technology, 2024)
This study aims to investigate the step-wedge phantom for calibrating CT localizer radiograph for different tube voltages. The in-house step-wedge phantom has five steps with thicknesses of 6, 12, 18, 24, and 30 cm. The phantom was scanned using a 64-slice Siemens Definition AS CT scanner at tube voltages of 80, 100, 120, 140, and 160 kVp. The relationship between pixel values (PV) and water-equivalent thickness (tw) was obtained for different step thicknesses. This relationship was used to calibrate the CT localizer radiograph for measuring water-equivalent (Dw) and size-specific dose estimate (SSDE). The results of Dw and SSDE from the localizer radiograph were compared with those calculated from axial CT images. It is found that tube voltage (kVp) can affect the accuracy of Water-Equivalent Diameter (DW) measurements in localizer radiograph imaging. Lower tube voltages tend to increase image contrast but may also increase noise, while higher voltages can reduce contrast while producing images with better penetration and higher radiation doses.